La revocación del reconocimiento de estatalidad en el Derecho Internacional - Rosales Zamora, Pablo; Ambrocio Gil, María (Pontificia Universidad Católica del Perú, 2023)
While there are extensive doctrinal reflections on the study of States in international law, there has been little interest in the analysis of the revocation of statehood recognition (derecognition) and its legal feasibility. Some scholars have argued that this is because such a phenomenon is purely theoretical and rarely observed in reality.Considering that there are prominent cases where the revocation of previously granted statehood recognition is evident, the most frequent being those of some “emerging states”, it is considered that the withdrawal of recognition deserves to be examined and criticized from the perspective of public international law; moreover, because the doctrine is a tool that can assist states in the examination of specific cases involving derecognition. States need to have guidelines that allow them to orient themselves in relation to the revocation of recognition and to know whether there are scenarios where it is considered possible to use this figure.In this sense, the authors aim to explore some of the probable contexts surrounding the revocation of recognition of statehood, offering a vision of this figure from the principle of good faith in public international law. Additionally, they propose a formula for the exceptional application of withdrawal of recognition in the context of premature recognition or the loss of some of the elements of statehood.

Si bien existen amplias reflexiones doctrinarias sobre el estudio de los Estados en el derecho internacional, casi no ha habido interés en el análisis de la revocación del reconocimiento de estatalidad (derecognition) y su viabilidad jurídica. Algunos estudiosos han argumentado que ello se debe a que tal fenómeno es puramente teórico y excepcionalmente perceptible en la realidad.Considerando que existen casos resaltantes donde se evidencia la revocación del reconocimiento de estatalidad previamente otorgado, siendo los más frecuentes aquellos de algunos “Estados emergentes”, se estima que el retiro del reconocimiento merece ser examinado y criticado desde el derecho internacional público; más aún, porque la doctrina es una herramienta que puede coadyuvar a los Estados en el examen de casos específicos que involucran el derecognition. Los Estados necesitan contar con pautas que les permitan orientarse con relación a la revocación del reconocimiento y saber si existen o no escenarios donde se considere posible emplear esta figura.En ese sentido, los autores persiguen explorar algunos de los probables contextos en torno a la revocación del reconocimiento de estatalidad, ofreciendo una visión de esta figura desde el principio de la buena fe en el derecho internacional público; además, proponen una fórmula de aplicación excepcional del withdrawal of recognition en el contexto de un reconocimiento prematuro o la pérdida de alguno de los elementos de estatalidad.
Keywords: Recognition; Statehood; Declarative theory; Constitutive theory; Derecognition; Reconocimiento; Estatalidad; Teoría declarativa; Teoría constitutiva; Derecognition; https://purl.org/pe-repo/ocde/ford#5.05.00